Searchlight trapping reveals seasonal cross-ocean migration of fall armyworm over the South China Sea - Xian-yong ZHOU; Qiu-lin WU; Hui-ru JIA; Kong-ming WU (Journal of Integrative Agriculture)
The fall armyworm (FAW), Spodoptera frugiperda, is a migratory noctuid pest that has recently invaded eastern Asia. From 2017 up till 2020, searchlight trapping was used to assess the extent of FAW migration across the South China Sea. Molecular and morphology-based identification confirmed that FAW made its first appearance on Yongxing Island on 11 April 2019, with most trapped individuals belonging to the S. frugiperda “corn-strain”. Carbon isotope analysis further showed that FAW moths originated from C4 host plants, while trajectory analyses revealed that migratory S. frugiperda adults are able to cross the South China Sea and enter mainland China. This long-distance migration process plausibly results in frequent genetic mixing between domestic FAW populations and those of neighboring Southeast Asian countries. Overall, this work provides unique insights into FAW migration across eastern Asia and ultimately can help advance pest forecasting, risk assessment and area-wide pest management.